Special Welfare and Ethical Requirements for Infectious Animal Experiments - MIN Fangui; FU Hongkun; LIU Yonggang; LIU Xiangmei; LIU Zhonghua; LI Yao; TAO Yufeng (Shiyan dongwu yu bijiao yixue)
Infectious disease animal models serve as indispensable tools for understanding the transmission patterns, pathogenesis, and anti-infective medicine. During the preparation and application of infectious animal disease models, situations inevitably arise that violate animal welfare and ethics, such as animal pain, suffering, and distress. Considering the biosafety factors, animal mortality is still used as the experimental endpoint in most experiments on infectious animals, which poses extremely high requirements for animal welfare and ethics. It is imperative to establish guiding principles or norms for the welfare and ethics of infectious animal experiments. Based on the fundamental principles of the welfare and ethics of experimental animals, this paper explores the special welfare and ethical requirements in infectious animal experiments. It emphasizes that infectious animal experiments should fully consider the balance among the scientific objectives of the research plan, animal welfare and ethics, and occupational health and safety of personnel. Based on literature research and comparative analysis of the welfare and ethical requirements of conventional animal experiments, special welfare and ethics requirements for infectious animal experiments are proposed, including personnel requirements, experimental animal selection standards, living environment management and equipment, special care and veterinary care, and humane endpoints. Personnel are required to undergo effective biosafety training, and sufficient authority should be granted to the Institutional Animal Care and Use Committee (IACUC), veterinarians, and veterinary technicians to ensure the implementation of animal welfare and ethics practices. The selection of laboratory animals should fully consider the requirements of research objectives, welfare, ethics, and biosafety, with the susceptibility and body size of laboratory animals being the key concerns in high-level biosafety laboratories. It is also clarified that the humane endpoint is an indispensable element of welfare and ethics in infectious animal experiments. Environmental enrichment and special care are necessary guarantees for achieving animal welfare and ethics. Therefore, this study can serve as a reference for relevant work.